Emergency peripartum hysterectomy in a tertiary hospital in Upper Egypt: six years analysis - Abbas, Ahmed M.; Abdelbadee, Ahmed Y.; Amin, Mariam T.; Abdelrahman, Reham M.; Tolba, Sara M.; Abdelkarim, Ahmed R.; Shahin, Ahmed Y.; Salman, Safwat A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Emergency peripartum hysterectomy (EPH) is often performed for life-threatening obstetric conditions especially when conservative treatment approach fails to stop postpartum hemorrhage. The aim of the study is to detect the incidence, indications, and complications of EPH over 6 years in Assiut Women Health Hospital in Upper Egypt. Methods: A historical cohort study conducted between January 2009 and December 2014. Detailed review of all files of cases of EPH including maternal age, parity, gestational age, type of delivery, indications for EPH and outcome of the hysterectomy. Results: The overall incidence of EPH was 1.30 per 1,000 deliveries. The main indications for hysterectomies were uterine atony 60 (48.78 %), abnormal placentation 27 (21.95 %) and rupture uterus 25 (20.32 %). There were 48 (39.02%) maternal deaths, while the perinatal mortality was 20.32% (25 cases). Using multivariate logistic regression analysis, we found that woman’s age ≥ 40 years and parity ≥ 5 were the most significant independent predictors for maternal mortality in cases of EPH (OR 5.49; 95% CI 2.16 - 13.96) and (OR 0.34; 95% CI 0.15 - 0.77) respectively. Conclusions: The incidence of EPH in Upper Egypt is high. Uterine atony is the major indication for EPH in our hospital. Late referral and delayed decisions to perform hysterectomy contributes in the high mortality rate.